The study of history based on local antiquity: A case study of existence of Kampar River in analyzing the past maritime in teaching history - Kamaruddin Kamaruddin; Ahmal Ahmal (Journal of Educational Sciences, 2018)
This paper describes the history-based learning local history, which takes the case of the existence of the Kampar River as local aspects in the learning of the maritime history in Indonesia. The data obtained through the triangulation by collecting interviews, observation, documentation study and  refered to articles, journals, textbooks and data other documents in the library that supported the teaching of history based on local history in the analyzing of maritime history in Indonesia, then it was investigated and drawn as a conclusion that the Kampar River was able to be used as the study of history in the local context in understanding of the teaching history in Indonesia related to maritime history. The results in this study show that first, Kampar River is a river that is loaded with historical events of the Kingdom of Sriwijaya, The Kingdom of Islamic until the independence of Indonesia. Second, the existence of Kampar River as a aspect of  emergence of history / local aspect which is able to be used as information about the maritime historyto the learners. For learning process, it involves local aspects of learners to connect, internalize and develop cooperation in analyzing of the concept aspects practicely in teaching maritime history. The concept of local history-based teaching history is contextually-learning learning concept that emphasizes the relevance of teaching materials with real world of learners. The existence of Kampar River is a means emergence of history / local aspect can be used as information about the maritime history to assist in the understanding of teaching maritime history on the learner, for learning involving local aspects for learners to connect, internalize and develop cooperation in analyzing aspects of the concept to praxis in teaching maritime history. The concept of local history-based teaching history is contextually-learning learning concept that emphasizes the relevance of teaching materials with real world of learners. The existence of Kampar River is a means emergence of history / local aspect can be used as information about the maritime history to assist in the understanding of teaching maritime history on the learner, for learning involving local aspects for learners to connect, internalize and develop cooperation in analyzing aspects of the concept practically in learning the maritime history. The concept of local history-based learning is contextually-learning that emphasizes the relevance of teaching materials with real world of learners.